2020
DOI: 10.1038/s41598-020-60745-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal contact guidance and YAP signaling on ultra-small nanogratings

Abstract: contact interaction of neuronal cells with extracellular nanometric features can be exploited to investigate and modulate cellular responses. By exploiting nanogratings (nGs) with linewidth from 500 nm down to 100 nm, we here study neurite contact guidance along ultra-small directional topographies. the impact of nG lateral dimension on the neuronal morphotype, neurite alignment, focal adhesion (fA) development and YAp activation is investigated in nerve growth factor (nGf)differentiating PC12 cells and in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 69 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…No change in cell alignment was visible after treatment with siRNA against YAP, but siRNA against TAZ led to an increased alignment (Raghunathan et al, 2014). More recently, Tonazzini et al (2020) similarly reported only a slight increase in YAP nuclear/cytoplasmic ratio in PC12 cells on nanogrooves, and no change in YAP expression levels (Tonazzini et al, 2020). Overall, these two studies suggest that YAP/TAZ pathway is only partially involved in contact guidance, at least in the response to grooves for these cell types.…”
Section: Yap-taz Signalingmentioning
confidence: 94%
“…No change in cell alignment was visible after treatment with siRNA against YAP, but siRNA against TAZ led to an increased alignment (Raghunathan et al, 2014). More recently, Tonazzini et al (2020) similarly reported only a slight increase in YAP nuclear/cytoplasmic ratio in PC12 cells on nanogrooves, and no change in YAP expression levels (Tonazzini et al, 2020). Overall, these two studies suggest that YAP/TAZ pathway is only partially involved in contact guidance, at least in the response to grooves for these cell types.…”
Section: Yap-taz Signalingmentioning
confidence: 94%
“…Contact guidance on 2D substrata like parallel grooves or adhesive ligand stripes has been intensively studied (recent examples include refs. [4][5][6] because in these experiments, the guidance field can be precisely defined and easily manipulated. However, it is the case of aligned fibrils that has the preponderance of physiological relevance.…”
mentioning
confidence: 99%
“…On the other hand, when it is greater than 75°, the neurite is scored as perpendicular to the cues. In the case of substrates without a topographic pattern, a random direction can be selected as the axis [ 71 , 80 ].…”
Section: Morphometric Analysis Of Model Eukaryotic Cells: B35 Neuroblastoma Cellsmentioning
confidence: 99%